Pola Makan Dan Status Gizi Perokok Di Sulawesi Tengah: Analisis Data Riskesdas 2018: Pola Makan dan Status Gizi Perokok di Sulawesi Tengah: Analisis Data Riset Kesehatan Dasar 2018 - Kurniasari, Dian; Galenso, Nitro; Hafid, Fahmi (Amerta Nutrition, 2024)
Background: According to the National Basic Health Research of Indonesia (Riskesdas) in 2018, the prevalence of non-communicable diseases (NCDs) in Central Sulawesi Province surpassed the national rate. This province is also home to 31.3% of active smokers. The main risk factor for NCDs is an unhealthy lifestyle such as physical inactivity, smoking, alcohol consumption, and unhealthy diet pattern. Objectives: This study aims to investigate diet patterns and nutritional status of adults in Central Sulawesi based on their smoking status. Methods: This is a cross-sectional study using data from Riskesdas 2018. Smoking status, diet pattern and nutritional status were the variables assessed from 12,211 respondents. The statistical analyses used in this study were chi-square test and Generalized Linear Model (GLM). Results: Thirty-six-point two per cent of the respondents were active smokers. The prevalence of overweight (BMI â‰¥25 kg/m2) and central obesity in smokers were significantly lower than that in the non-smoker group (p<0.05). The smoker group consumed sweetened drinks at least once a week, which increased the prevalence ratio as the weekly consumption frequency increased (PR=1.17 to 1.49; p<0.05). They also had a lower prevalence ratio of consumption a maximum of 3-4 portions/day of vegetable and consuming salty food (high sodium) 1-2 times a week. Conclusions: Although the prevalence ratio of overweight and central obesity are lower in smokers, they have unhealthy diet patterns, which are shown in lower consumption of vegetables and high in salty food. In the future, an advanced longitudinal study with representative number of respondents is needed to explore the causality of these variables.